Services for the prevention and treatment of dependence on alcohol and other drugs : fourteenth report of the WHO Expert Committee on Mental Health ; [meeting, Geneva 4 - 10 October 1966]. - World Health Organization (Geneva : WHO, 1967)
Hoe voorkom je verslaving aan alcohol en andere drugs?